Coupling coordination evaluation and influencing factors analysis of older adult care service resource supply and demand in China - Guo, Lingxiao; Wei, Hua; Tao, Qunshan; Chen, Kunyu (Frontiers in Public Health, 2025)
BackgroundThe coupling coordination development between the supply and demand of older adult care service resources represents a critical pathway for the deep integration of the “Healthy China” initiative and the strategy of “actively responding to population aging,” and holds significant importance for achieving the modernization transformation of the older adult care service system. However, China’s current older adult care service system continues to face substantial challenges, including structural imbalances between supply and demand and uneven regional development. There is an urgent need to systematically evaluate the coupling coordination level between these two systems and identify key influencing factors to provide theoretical support for evidence-based decision-making.MethodsBased on panel data from 31 provinces and municipalities in China spanning 2014–2023, this study employs the entropy weight method to construct a comprehensive evaluation index system for the supply and demand of older adult care service resources. The coupling coordination degree model is utilized to measure the coordinated development level between the two systems, and a Tobit panel model is applied to identify key factors influencing coupling coordination development.ResultsThe coupling coordination degree between the supply and demand of older adult care service resources in China exhibits an overall upward trend, having advanced from the verge of imbalance to barely coordinated status; however, the overall level remains relatively low. The spatial pattern demonstrates a significant “high in the east, low in the west” distribution characteristic, with the eastern region having reached primary coordination level, while the central and western regions predominantly remain in a supply-lagging imbalanced state. Economic development level emerges as the primary driving factor affecting coupling coordination, with science and technology expenditure, social capital investment, and education level all playing significantly positive roles, while the efficiency of government fiscal expenditure requires improvement.ConclusionTo enhance overall coordination levels and achieve balanced regional development, policymakers should formulate differentiated development strategies based on local resource endowments, optimize the collaborative mechanism between supply and demand of older adult care service resources, improve cross-departmental collaborative governance systems, and promote high-quality development of the older adult care service system.